Optimizing Human Capital in the Era of AI Advancements : Strategi for the Future Workforce - Ruslaini Ruslaini; Dadang Irawan; Farah Qalbia; Seger Santoso (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This research aims to explore strategies for maximizing human capital in the context of advancing artificial intelligence (AI) technologies within the workforce. The study employs a phenomenological approach to understand individuals' experiences and perceptions regarding AI integration in the workplace. Through purposive sampling, data were gathered from a diverse pool of professionals across industries. Semi-structured interviews were conducted to delve into participants' perspectives on the impact of AI on job roles, skill requirements, and organizational dynamics. Thematic analysis was employed to identify recurring patterns and emergent themes within the qualitative data. Preliminary findings suggest a nuanced interplay between AI technologies and human capabilities, highlighting the need for upskilling, retraining, and fostering adaptability among employees. The study contributes to the discourse on optimizing human resources amidst rapid technological advancements, offering insights for organizational strategies to harness the synergy between human expertise and AI innovations in the future workforce.